Cambridge One LMS in Enhancing Students' Learning Outcomes and Interest in English Final Test (A case study on English learning in 3rd graders at a Bilingual Elementary School in Semarang) - Yusefrizarukmini Yusefrizarukmini; Andang Saehu; Aminudin Zuhairi (Edumaspul: Jurnal Pendidikan, 2024)
The research focused on using Cambridge One LMS as an e-learning platform for Grade 3 English students at Semesta Bilingual Elementary School in Semarang. The main aim was to understand teachers' and students' challenges when using the Cambridge One LMS for English learning and find solutions. The researcher interviewed school principals, curriculum representatives, 2 English teachers, and four students from grades 3B and 3C at Semesta Bilingual Elementary School to collect data. The researcher also gave questionnaires to 40 students from classes 3B and 3C using Google Forms. Additionally, the researcher observed how Cambridge One LMS was used in English lessons. The questionnaire results showed that students positively viewed using the Cambridge One LMS for English lessons. However, the interviews revealed that teachers faced difficulties due to a lack of knowledge of technology, and the students had limited access to the Internet and computers or laptops. To address this, the school ensures effective use of the Cambridge One LMS by organizing workshops or training sessions provided by itself or a Cambridge representative. It offers comprehensive user guides or online tutorials for detailed instructions and access to support resources, such as help desks or customer support, which becomes beneficial for teachers' guidance. The school encourages collaboration among teachers familiar with the system to offer additional insights. Allowing time to explore the platform helps teachers become more comfortable and proficient. Finally, the school requests parents provide students with a computer or laptop for home use. Additionally, the school will enhance internet access and expand the computer lab facilities to support the teaching and learning process.